Domestic animal behaviour and welfare - Broom, Donald M., (CABI, 2007)
This book contains chapters on the behaviour and welfare of domestic animals, including dogs, cats, rabbits, furbearing animals, fishes, turkeys, ducks, geese and other livestock. The 36 chapters are divided into 6 main sections that discuss concepts and methods of measuring behaviour, organization of behaviour, social and reproductive behaviour, early and parental behaviour and abnormal behaviour management in relation to animal welfare.